Stenmuren i landskapet - Bylander, Anneli (2008)
The landscape with its associated historical tracks and remains are an important part of our cultural heritage that we consider important to conserve. The stone walls are an example of historical remains that helps to build up this cultural heritage. It is a landscape element that today usually is being associated with the old cultivated landscape, where they mainly functioned as boundary markings and fences. Today, the stone wall is a valuable element in the landscape with ecological, culture-historical and aesthetic values. Since the stone walls arose as elements in the landscape a lot has been changed within the agriculture. An ongoing rationalization along with the urbanization has done the cultivation of the landscape wider and less variated. Bigger resources have done that one despite smaller labor can farm the land more effective. Landscape elements like the stone wall have during this process unfortunately been put aside for a more effective agricultural production. The conserving of the heritage landscape with the historical landscape elements and the environments is today in many respects depending on a ongoing tradition and management according to old cultivation methods.